Antimicrobial herbal hand wash - Veloo Kutty, Rajaletchumy; Gopal, Kirthana; Eh Chaw, Yaneesa Vetsandonphong; William Santhiagu, Michelle (2021)
Microbes are the contributing factor to many diseases. Proper hand washing practices are critical in prevention of infection and spread of disease through direct contact. However, frequent hand washing has a link with the occurrence of contact dermatitis because hand wash available in the market consist of harsh chemicals which makes the skin prone to dryness, cracks and irritation. Antimicrobial agent like triclosan is banned due to its harmful adverse effects and safety issues. Hence, the demand of a new antimicrobial agent from natural source has increased. Therefore, the goal of this study is to formulate antimicrobial Hand wash Organoleptic pH study Viscosity (cP) Foam height(cm) Emolliency test Cleansing efficiency herbal foaming hand wash along with other mild ingredients.